If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -8 = 10x + 6 Reorder the terms: -8 + 8x = 10x + 6 Reorder the terms: -8 + 8x = 6 + 10x Solving -8 + 8x = 6 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -8 + 8x + -10x = 6 + 10x + -10x Combine like terms: 8x + -10x = -2x -8 + -2x = 6 + 10x + -10x Combine like terms: 10x + -10x = 0 -8 + -2x = 6 + 0 -8 + -2x = 6 Add '8' to each side of the equation. -8 + 8 + -2x = 6 + 8 Combine like terms: -8 + 8 = 0 0 + -2x = 6 + 8 -2x = 6 + 8 Combine like terms: 6 + 8 = 14 -2x = 14 Divide each side by '-2'. x = -7 Simplifying x = -7
| 15+2.00x=15 | | 3ln(5x)=15 | | 3(w-5)=-4w-22 | | -3x-8=-53+2x | | 18=x+(1.15x) | | -8+5w=-18 | | 2(5x+10)=6x-8 | | 2(y-2)-4y=2 | | 2x^2+3x=70 | | 32q-72=0 | | 3b+7a=-5b-62a | | 10+5c-15=-7 | | u^3-4u-24=0 | | 5+x=3x-5 | | N-7=16-2 | | N-7=16-3 | | 64x^2-80x+25y^2= | | 4+5x=-5x+74 | | 13-6=x | | 3.66X+Y=3 | | (-2.2)-(-6.7)=x | | -4(u+2)=-7u-23 | | c=16+0.40(x-90) | | 7x^2+3x+j=0 | | c=12+0.40(x-90) | | C=8+0.40(x-90) | | 100b^2-81= | | 7-3x=x+3 | | 4(3b-1)=5(2b+3) | | -76+12x=5x+29 | | 5.5x=0.1(4x+10) | | 7-7y=5 |